Pelos trilhos da ilustração: reinscrever a natureza na cidade - Melão, Dulce (2021)
This paper aims to shed light on ways of reinscribing nature in the city, through the paths of illustration in the picturebook Florette, by Anna Walker, focusing on: i) the dimensions assumed by the city as a multifaceted space seen through the eyes of a child; ii) the role of illustration to enhance the understanding of the plurisignificant nature of interior and exterior spaces and the ways in which rebuilds commitment to the common good. In order to meet these goals, the following will be analysed: i) the role of peritexts to unfold the relevance to care for nature, within the city, and how overflows to the thresholds of the page; ii) the multiple dimensions assumed by the centrality of the illustration to create a synergistic relationship with the narrative, exploring the importance of this relationship for the drawing of a plethora of details that stand out on the page (unveiling the eruption of nature in the city). The conclusions highlight the unique nature of the possibilities inherent in the action of each person for the commitment to the common good, at the heart of the objectives of sustainable development. The challenges that are implicit in it, embodied in the itinerary undertaken by the main character of the picturebook, reveal delicate modes of resilience that thrive throughout the reading and flow into communion with nature.